Wacana Tanding Stereotype Gender Dalam Iklan Heineken – Cheers To All (Analisis Semiotika Roland Barthes) - Manurung, Samuel Oktaberian; Joni, I Dewa Ayu Sugiarica; Pradipta, Ade Devia; Damasemil, Calvin (E-Jurnal Medium, 2023)
An understanding of gender often creates pros and cons in society, coupled with the existence of stereotypes attached to each gender, makes issues about gender are more interesting to discuss. One of them is a campaign ad released by the Heineken company entitled Cheers To All in 2020 on their YouTube page. The purpose of this research is to explain the Discourse of Countering Gender Stereotypes in Heineken-Cheers To All Advertisements. To achieve this goal,  this  research  uses  qualitative  methods  and  constructivism  paradigms  with  semiotic analysis proposed by Roland Barthes by looking at the value of denotation, connotation and myth. As a result of this study, Heineken tries to fight against gender stereotypes that have been attached to food and beverages, especially in beers and cocktails which are depicted through scenes that try to show that Heineken is openly against the existing stereotypes and has been stuck in society.